Jewish identity in early rabbinic writings - Stern, Sacha. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1994)
Jewish Identity in Early Rabbinic Writings is more than a question of legal status: it is the experience of being Jewish or of 'Jewishness' in all its social and cultural dimensions. This work describes this experience as it emerges in Talmudic and Midrashic sources. Besides the question of "who is a Jew?", topics include the contrast between Israel and the non-Jews, the physical embodiment of Jewish identity, the 'boundaries' of Israel and resistance to assimilation. Jewish identity, it is argued, hinges essentially on the Divine commandments ( mitzvot ) and on Israel's perceived proximity with the Divine. Drawing on a variety of disciplines, including the theories of William James and Merleau-Ponty, this study raises important issues in anthropology, as well as accounting for central aspects of early rabbinic Judaism.